Uterine displacement as fertility sparing technique for pelvic malignancies: Demonstration of the surgical options on a human cadaver - Matteo Pavone; Lise Lecointre; Barbara Seeliger; Nicolò Bizzarri; Jacques Marescaux; Giovanni Scambia; Cherif Akladios; Denis Querleu (Elsevier, 2024)
Preservation of fertility without compromising oncological outcomes is a major objective in young patients at the time of cancer treatment (Azaïs et al., 2018; Bizzarri et al., 2022). Radio(chemo)therapy is often required in pelvic malignancies (anus, rectum, sarcoma). Direct irradiation results in a damage to ovarian (Bizzarri et al., 2023) and endometrial function (Lohynska et al., 2021), compromising the fertility of female patients of reproductive age. While ovarian transposition is an established method to move the ovaries away from the radiation field (Morice et al., 2022; Pavone et al., 2023), corresponding surgical procedures displacing the uterus are investigational (Pavone et al., 2023; Querleu et al., 2010; Ribeiro et al., 2017, 2024). In a human female cadaver model, the reported laparoscopic techniques of uterine displacement were carried out to demonstrate their feasibility and the step-by-step surgical techniques. The surgeries were performed in a hybrid operating room which enables to perform CT-scan and evaluate the uterine positions according to anatomical landmarks. The following procedures were performed in the same cadaveric model and were described in the video: 1. Uterine suspension of the round ligaments to the abdominal wall 2. Uterine ventrofixation of the fundus at the level of the umbilical line 3. Uterine transposition according to the technique reported by Ribeiro et al. All procedures were completed without technical complications. All of these uterine displacement procedures are technically feasible. Uterine transposition is the most technically complex procedure, and its effectiveness in protecting the endometrium should be evaluated in comparison to the simpler techniques (Table 1). Future studies incorporating radiotherapy simulations are needed to define which technique represents the best compromise between surgical complexity and positioning the uterus at a level that receives the lowest possible radiation dose.